How to win the political contest: a monopolist vs. environmentalists - Graichen, Patrick (Discussion paper series, 1999)
This paper sheds light on the political economy of local energy politics both from a theoretical and an empirical perspective. A case study of a small town in Southern Germany (Schönau) is presented, where environmentalists have won the political contest against the regional energy monopolist and have founded an energy supply firm themselves.
Keywords: Arbeitspapier; Graue Literatur; Umweltgefährdung; Energiepolitik; Rent Seeking